2010
DOI: 10.3928/01477447-20100129-33
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Trigger Thumb in Identical Twins: Congenital or Acquired?

Abstract: Pediatric trigger thumb is an uncommon condition with a calculated incidence of 3 per 1000 live births or less. Some reports have suggested a congenital etiology while others could not find a single case of pediatric trigger thumb at birth. This article reports the occurrence of bilateral trigger thumbs in identical twins, age 3 years and 9 months, affecting their thumbs to similar extents, which may suggest a congenital etiology.Congenital etiology for trigger thumb has been proposed for many reasons: occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…While much has been discussed about the pathophysiology of the congenital trigger thumb, the debate continues about its cause: a genetic versus acquired etiology. Some studies in the literature lean towards a genetic cause for the condition [3,[8][9][10][11], whereas others argue that it may be acquired in nature [12,13]. Regardless of the true cause of the condition, it is possible that some children are born with the condition but it manifests later in infancy or childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While much has been discussed about the pathophysiology of the congenital trigger thumb, the debate continues about its cause: a genetic versus acquired etiology. Some studies in the literature lean towards a genetic cause for the condition [3,[8][9][10][11], whereas others argue that it may be acquired in nature [12,13]. Regardless of the true cause of the condition, it is possible that some children are born with the condition but it manifests later in infancy or childhood.…”
Section: Discussionmentioning
confidence: 99%
“…The few articles available in the literature on this topic suggest that genetic factors are important in its etiology [5-8, 10, 11]. There are three case reports of "congenital trigger thumb" in twins [3,4,8] that support the genetic factors in the etiology of the condition. These reports are based on the fact that the condition occurred in "identical" twins but without a proof of the monozygotic nature of the twins with DNA analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested a possible congenital predisposition, based on the observation that the lesion is sometimes present at birth [2,[9][10][11][12][13] or shortly afterwards, along with a high incidence of bilateral occurrence in children and the occurrence in monozygotic twins [11,14,15]. Some authors believe that CTT is familial [12,16].…”
Section: Introductionmentioning
confidence: 97%
“…Its incidence within the first year of life (3.3/ 1000) exceeds that of both clubfoot and developmental dysplasia of the hip. [9][10][11][12][13][14] Thickening and hypervascularization of the A1 pulley are the hallmarks of trigger fingers on sonography in adults. 2,3 Proposed etiologies include trauma, infection, congenital soft-tissue malformation, intratendinous nodules, or articular malformation.…”
Section: Introductionmentioning
confidence: 99%